9x + 26 + 7x - 17 = 2x + (-3x) + 5x

Question

Asked 2/13/2013 12:02:09 PM

Updated 5/28/2014 11:59:42 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [5/28/2014 11:58:34 PM]

Rating

3

9x + 26 + 7x - 17 = 2x + (-3x) + 5x

16x + 9 = 4x

16x - 4x = -9

12x = -9

x = -9/12 = -3/4

16x + 9 = 4x

16x - 4x = -9

12x = -9

x = -9/12 = -3/4

Added 5/28/2014 11:59:42 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/29/2014 1:04:44 AM]

27,092,264

questions answered

There are no comments.